Pengembangan Permukiman Berbasis Ekowisata di Pulau Pannikiang, Kabupaten Barru - Andi Evi Lestari; Wiwik Wahidah Osman; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
The existence of ecotourism has a positive influence on the surrounding community, especially in the settlements of Pannikiang Island in terms of improving the welfare of the population. This research is intended to formulate directions for the development of ecotourism-based residential areas on Pannikiang Island, Barru Regency. The integration of the direction of the development of ecotourism-based settlements on Pannikiang Island Barru Regency is done by increasing the welfare of the island's population through the potential of the region while involving the community in ecotourism. The analytical method used in this research is descriptive qualitative analysis, quantitative descriptive, comparative and spatial analysis. Based on the results of the analysis, the direction of the development of ecotourism-based settlements on Pannikiang Island, among others, the direction of settlements as supporting accommodations for dual-function ecotourism, namely by selling processed marine and mangrove products, improving the quality of facilities and infrastructure supporting ecotourism and the direction of community-based ecotourism development.